Volatile Compounds and Total Phenolic Content of Perilla frutescens at Microgreens and Mature Stages - Rosanna Dimita; Samar Min Allah; Andrea Luvisi; Davide Greco; Luigi De Bellis; Rita Accogli; Carlo Mininni; Carmine Negro (Horticulturae, 2022)
Microgreens are considered products of high biological value because they contain natural and beneficial metabolites and antioxidants in high amounts; also, consumers appreciate them very much for their aromas. In this work, we focused our attention on the volatile organic compounds (VOCs) emitted from whole fresh leaves of two Chinese basil varieties (Perilla frutescens var. frutescens and var. crispa) at the microgreens stage; to show that the emission is microgreens specific we tested whether this capacity remains during subsequent growth of the plants. We found differences between the VOCs produced by the leaves of the two varieties at the microgreens stage and significantly reduced emission after development (additional four weeks of growth) particularly for the green variety (var. frutescens). The main volatiles emitted by whole leaves were D-Limonene for the red variety (crispa) and 2-Hexanoylfuran for the green one. In addition, the total phenolic content (TPC) and antioxidant power increase in adult leaves. These results clearly indicate that the particular smell of microgreens Perilla leaves depends on the specific variety and is not related to the amount of total phenols or antioxidant capacity of the leaves.